2016
DOI: 10.1016/j.jbi.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Health at hand: A systematic review of smart watch uses for health and wellness

Abstract: Consumer-grade smart watches have penetrated the health research space rapidly since 2014. Smart watch technical function, acceptability, and effectiveness in supporting health must be validated in larger field studies that enroll actual participants living with the conditions these devices target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
156
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(189 citation statements)
references
References 20 publications
1
156
0
2
Order By: Relevance
“…An analysis of 73 studies conducted between 2014 and 2016 showed that watches focused on activity and heart rate monitoring, speech therapy adherence, diabetes self-management, and detection of seizures, tremors, scratching, eating and medication-taking behaviours. The paper concluded that more studies are required to really evaluate the efficacy of smart watches [15]. This requirement may be addressed in Electronics 2020, 9, 275 3 of 21 part by a National Institute of Health (NIH) survey into precision medicine earmarked to start later in 2020 [16].…”
Section: Using the Cellphone Networkmentioning
confidence: 99%
“…An analysis of 73 studies conducted between 2014 and 2016 showed that watches focused on activity and heart rate monitoring, speech therapy adherence, diabetes self-management, and detection of seizures, tremors, scratching, eating and medication-taking behaviours. The paper concluded that more studies are required to really evaluate the efficacy of smart watches [15]. This requirement may be addressed in Electronics 2020, 9, 275 3 of 21 part by a National Institute of Health (NIH) survey into precision medicine earmarked to start later in 2020 [16].…”
Section: Using the Cellphone Networkmentioning
confidence: 99%
“…Examples of intuitive‐level responses include heart rate, breathing rate, galvanic skin response, or evaluation of state anxiety at that moment. Data collection on in‐the‐moment intuitive processes can be facilitated by mobile surveys and new sensor technologies (Reeder & David, ). Intuitive‐level data may provide researchers a better understanding of the biopsychosocial variables occurring at the moment of decision and suggest novel intervention pathways.…”
Section: Two Minds Theorymentioning
confidence: 99%
“…Intuitive-level responses will be more predictive of actual behavior than narrative responses because narrative responses are only one consideration to future intuitive choices. When data are collected in the moment of a decision, the data likely reflect an Intuitive response (Cook, Schmiege, Starr, Carrington, & Bradley-Springer, 2017 (Reeder & David, 2016). Intuitive-level data may provide researchers a better understanding of the biopsychosocial variables occurring at the moment of decision and suggest novel intervention pathways.…”
Section: Implications For Nursingmentioning
confidence: 99%
“…Most of these platforms use RESTful API to provide users with collected data, and users can easily obtain their data through simple identification process and a URL. Owing to the evolution of wearable devices, there is a growing application of this technology to medical and healthcare studies using data obtained through wearable devices in place of medical devices [33]. Sensor technology coupled with wearable devices is already producing significant findings from studies, 3 Journal of Sensors and users can be provided with diverse healthcare services by integrating clinical data obtained from sensors on a cloud.…”
Section: Healthcare Platform and Analysismentioning
confidence: 99%